Occupational class differences in ankle-brachial index and pulse wave velocity measurements to detect subclinical vascular disease - Ferrario, Marco Mario; Martire, Giulia; Gianfagna, Francesco; Lasalvia, Paolo; Cremonesi, Federico; Tozzi, Matteo; Franchin, Marco; Campana, Francesca; Roncaioli, Mattia; Cavicchiolo, Marco; Borchini, Rossana; Iacoviello, Licia; et al. (La Medicina del Lavoro, 2021)
Background: High pulse wave velocity (PWV) and low ankle brachial index (ABI) have been proposed as surrogate end-points for cardiovascular disease (CVD). Objectives: In a cross-sectional setting, we aimed at assessing the distributions of PWV and ABI among occupational classes (OC) in a population-based ever-employed salaried sample. Methods: We enrolled 1388 salaried CVD-free workers attending a CVD population-based survey, the RoCAV study, and classified them into four OC, based on current or last job title: manager/director (MD), non-manual (NMW), skilled-manual (SMW) and (UMW) unskilled-manual workers. We derived brachial-ankle PWV and ABI from four-limb blood pressures measurements, then carotid-femoral PWV (cfPWV) was estimated. We estimated the OC gradients in cfPWV and ABI using linear and logistic regression models. Results: Compared to MD (reference category), UMW had higher age- and BMI-adjusted cfPWV mean values both in men (0.63 m/s; 95%CI:0.11-1.16) and women (1.60 m/s; 0.43-2.77), only marginally reduced when adjusting for CVD risk factors. Decreased ABI mean values were also detected in lower OC. The overall detection rate of abnormal cfPWV (≥12 m/s) or ABI (≤0.9) values was 28%. Compared to MD, the prevalence of abnormal cfPWV or ABI was higher in NMW (OR=1.77; 95%CI:1.12-2.79), SMW (1.71; 1.05-2.78) and UMW (2.72; 1.65-4.50). Adjustment for CVD risk factors used in risk score equations did not change the results. Discussion: We found a higher prevalence of abnormal values of arterial stiffness measures in lower OC, and these differences were not explained by traditional CVD risk factors. These may be presumably determined by additional work- and environmental-related risk factors.